Flipbook Integrating Balinese Folklore-Based Local Wisdom to Enhance Elementary Students’ Science and Social Studies (IPAS) Learning Outcomes - Ni Nyoman Satriani; I Made Citra Wibawa; Ida Bagus Putu Arnyana (Journal of Education Reseach and Evaluation, 2026)
This study aimed to develop and examine the feasibility of a flipbook-based learning medium incorporating local wisdom from Balinese folktales for IPAS instruction, particularly for fifth-grade elementary school students. This study employed a research and development approach using the ADDIE model. The feasibility of the developed product was evaluated by two subject-matter experts and two instructional media experts. Practicality testing was conducted with five teachers and twenty-five sixth-grade students who participated in the trial and provided assessments of the flipbook. Data were collected using questionnaires and objective tests, with questionnaires serving as the primary research instrument. Data analysis techniques included quantitative descriptive analysis, qualitative descriptive analysis, and inferential statistical analysis using Analysis of Covariance (ANCOVA). The results showed that the flipbook achieved a validation score of 92.5% from media experts and 93.33% from content experts, indicating a very high level of validity. The practicality assessment yielded mean scores of 4.81 from teachers and 4.78 from students, categorizing the media as very practical for instructional use. Hypothesis testing revealed a highly significant effect on students’ learning outcomes. It can be concluded that the use of a flipbook-based learning medium integrating Balinese folktale local wisdom significantly improves the IPAS learning outcomes of fifth-grade elementary school students. The implication of the research is that the flipbook media containing local wisdom of Balinese folk tales that was developed can help students in learning.